Dimensional effects of polymer pillar arrays on hydrophobicity. (1st February 2016) - Gao, J.; Zhao, J.; Liu, L.; Xue, W.
Abstract : This paper reports experimental studies on the dimensional effects of pillar arrays on surface hydrophobicity. Completely different behaviours are observed on intrinsically hydrophobic and hydrophilic materials. In order to experimentally observe the Cassie-to-Wenzel transition, circular pillar arrays with varying diameters and spacing are fabricated on PDMS and SU-8 surfaces. Wetting experiments show that the PDMS arrays demonstrate clear Cassie-to-Wenzel transition as the spacing increases. The critical transition spacing for different diameters shows a close match to theoretical predictions based on a force balance model. The transition model also predicts the maximum contact angles. By comparison, the dimensional effects on an intrinsically hydrophilic surface (SU-8) show smaller contact angles without a transition phase. These differences come from the inherent wettability of the two polymers. Without further coatings or treatment, the PDMS structures can achieve contact angles close to 170° while the SU-8 arrays can only achieve contact angles up to 140°.